Implementasi Konsep “Kudus Explore : Exploring With Experiencing” pada Perancangan Interior Museum Kebudayaan Kudus - Iriene Cahyani Santoso; Ronald Hasudungan Irianto Sitindjak; Stephanie Melinda Frans (Intra, 2019)
Kudus is known as a region that has abundant historical and cultural records, yet there hasn’t been a place which can accommodate and represent the city of Kudus as a whole. The thematic museum available is still conventional. Therefore the Kudus Cultural Museum is designed with a recreational, educational, and interactive look. The method used is Design Thinking Method which uses three stages, which are Inspiration, Ideate and Implementation. The design concept for the Kudus Cultural Museum is